"The Twelve Chairs": Real and Unreal Onyms - Saghyan, Bella (Bulletin of Yerevan University H: Russian Philology, 2023)
The article is devoted to the study of onomasticon as an integral part of a work of art that conveys communicatively significant information and acquires new meanings in the process of functioning in the text and the perception of the text by the reader. Proper names – onyms are used both in the language and in the literary text, make it possible to study the changes in the language system that are caused by historical, social and cultural events typical to the given society. The article is devoted to the study of real and fake onyms in the novel by I. Ilf and Y. Petrov "The Twelve Chairs". The aim of the article is to determine the semantics and functions of onyms in a work of art, to identify their role in the semantic and structural organization of the text, to ensure its informativeness and integrity, to show the dependence of the use of onyms of various groups in connection with the artistic context and author's tasks. Almost all types of onyms are considered, which are divided into real and fake. Along with real-life onyms, the authors use a large number of fake onyms that reflect the spirit and life of that time, create illusions of reality in the novel. Varieties of proper names are analyzed, differing in the types of named objects and in the principles of nomination. The contribution that they make to the artistic fabric of the novel is investigated; the characteristic of proper names is given in the aspect of their fulfillment of artistic functions in this work.
Keywords: I. Ilf; E. Petrov; The Twelve Chairs; proper names; onomasticon; real onyms; unreal onyms